1985
DOI: 10.1172/jci111935
|View full text |Cite
|
Sign up to set email alerts
|

Control of sodium and potassium transport in the cortical collecting duct of the rat. Effects of bradykinin, vasopressin, and deoxycorticosterone.

Abstract: Several factors interact to maintain precise control of electrolyte transport in the mammalian cortical collecting duct. We have studied the effects of deoxycorticosterone, arginine vasopressin, and bradykinin on net transepithelial sodium and potassium transport in isolated, perfused rat cortical collecting ducts. Chronic administration of deoxycorticosterone to rats increased both sodium absorption and potassium secretion above very low basal levels. Consequently, deoxycorticosterone-treated rats were used f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
165
1
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(186 citation statements)
references
References 33 publications
19
165
1
1
Order By: Relevance
“…This finding is consistent with previous reports that isolated, perfused rat CCTs do not exhibit electrogenic, amiloride-sensitive Na reabsorption unless the mineralocorticoid levels are raised (Tomita, Pisano, and Knepper, 1985;Reif, Troutman, and Schafer, 1986). The rat colon shows a similar pattern of transepithelial transport.…”
Section: Dependence Of Na Channel Activity On Dietsupporting
confidence: 93%
“…This finding is consistent with previous reports that isolated, perfused rat CCTs do not exhibit electrogenic, amiloride-sensitive Na reabsorption unless the mineralocorticoid levels are raised (Tomita, Pisano, and Knepper, 1985;Reif, Troutman, and Schafer, 1986). The rat colon shows a similar pattern of transepithelial transport.…”
Section: Dependence Of Na Channel Activity On Dietsupporting
confidence: 93%
“…Accordingly, we have shown that TK activates the epithelial Na + channel ENaC by cleaving its gamma subunit (34). In CCDs isolated from rats microperfused in vitro, Tomita et al (35) showed that basolateral bradykinin inhibits net Na + absorption by affecting an electroneutral, amiloride-resistant, thiazide-sensitive NaCl transporter that remained unidentified until our recent report (35). In this study, we observed that CCDs from TK −/− mice actually absorb sodium via an electroneutral process.…”
Section: Discussionmentioning
confidence: 50%
“…Whereas AVP produces a persistent increase in JNa in the rat (39,40), it only transiently stimulates JNa and VT in the rabbit (21,27,41). The biphasic effect of vasopressin action on VT and JNa in the rabbit CCD has been attributed to prostaglandin production in the rabbit CCD (21).…”
Section: Discussionmentioning
confidence: 99%